The Role of Human Papilloma Virus in Dictating Outcomes in Head and Neck Squamous Cell Carcinoma - Brennan, Shane; Baird, Anne-Marie; O’Regan, Esther; Sheils, Orla (Frontiers in Molecular Biosciences, 2021)
The Human Papilloma Virus (HPV) is an oncogenic virus which is associated with the development of head and neck squamous cell carcinoma (HNSCC), predominantly within the oropharynx. Approximately 25% of oropharyngeal squamous cell carcinoma (OPSCC) cases worldwide are attributable to HPV infection, with an estimated 90% in the United States. Transmission is via exposure during sexual contact, with distinctive anatomical features of the tonsils providing this organ with a predilection for infection by HPV. No premalignant lesion is identifiable on clinical examination, thus no comparative histological features to denote the stages of carcinogenesis for HPV driven HNSCC are identifiable. This is in contrast to HPV-driven cervical carcinoma, making screening a challenge for the head and neck region. However, HPV proffers a favorable prognosis in the head and neck region, with better overall survival rates in contrast to its HPV negative counterparts. This has resulted in extensive research into de-intensifying therapies aiming to minimize the morbidity induced by standard concurrent chemo-radiotherapy without compromising efficacy. Despite the favorable prognosis, cases of recurrence and/or metastasis of HPV positive HNSCC do occur, and are linked with poor outcomes. HPV 16 is the most frequent genotype identified in HNSCC, yet there is limited research to date studying the impact of other HPV genotype with respect to overall survival. A similar situation pertains to genetic aberrations associated in those with HPV positive HNSCC who recur, with only 4 published studies to date. Somatic mutations in TSC2, BRIP1, NBN, TACC3, NFE2l2, STK11, HRAS, PIK3R1, TP63 and FAT1 have been identified in recurrent HPV positive OPSCC. Finding alternative therapeutic strategies for this young cohort may depend on upfront identification of HPV genotypes and mutations which are linked with worse outcome, thus ensuring appropriate stratification of treatment regimens.